2015
DOI: 10.1177/0363546515589108
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Comparison of the Pediatric Versus Adult IKDC Subjective Knee Evaluation Form in Adolescents

Abstract: There was no clinically significant difference between the pediatric and adult IKDC form scores in adolescents aged 13 to 17 years. This result allows use of whichever form is most practical for long-term tracking of patients. A simple linear equation can convert one form into the other. If the adult questionnaire is used at this age, it can be consistently used during follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 18 publications
1
46
0
Order By: Relevance
“…To our knowledge, for this demographic the IKDC is the only known adult PROM that has been secondarily shown to be translatable to the pediatric version in adolescent athletes. 45 In a study by Oak et al, 38 the adult and pediatric forms of the IKDC were shown to be significantly different by 1.5 points, although this difference was not clinically significant. The authors concluded that the adult version of the IKDC could be used in adolescents aged 13 to 17 years.…”
Section: Discussionmentioning
confidence: 95%
“…To our knowledge, for this demographic the IKDC is the only known adult PROM that has been secondarily shown to be translatable to the pediatric version in adolescent athletes. 45 In a study by Oak et al, 38 the adult and pediatric forms of the IKDC were shown to be significantly different by 1.5 points, although this difference was not clinically significant. The authors concluded that the adult version of the IKDC could be used in adolescents aged 13 to 17 years.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study showed that the Pedi-IKDC and the IKDC had statistically similar scores when administered to a group of adolescent patients with knee injuries. 28 The Pedi-IKDC questionnaire was mailed to eligible patients, and if they did not return the questionnaire or opt out of the study within 2 weeks, then they were called and invited to complete the questionnaire over the phone. For patients who did not complete the Pedi-IKDC by mail or over the phone, their clinical IKDC scores were used, as the IKDC questionnaire is routinely completed by patients during clinic as part of standard care.…”
Section: Methodsmentioning
confidence: 99%
“…Used in isolation, individual outcome measures can provide helpful clinical information, but how these measures relate to each other may offer a stronger clinical picture of the patient's actual recovery from surgery. A number of investigators 30,38,39 have assessed the association between self-reported outcomes and functional measures after ACLR. Logerstedt et al 19 found that lower IKDC scores suggested poor isometric quadriceps strength during functional testing for clearance to return to activity.…”
Section: Discussionmentioning
confidence: 99%